2015
DOI: 10.1007/s12011-015-0348-x
|View full text |Cite
|
Sign up to set email alerts
|

The Co-induced Effects of Molybdenum and Cadmium on Antioxidants and Heat Shock Proteins in Duck Kidneys

Abstract: Molybdenum (Mo) is an essential element for human beings and animals; however, high dietary intake of Mo can lead to adverse reactions. Cadmium (Cd) is harmful to health. To investigate the toxicity of Mo combined with Cd in duck kidneys, 240 ducks were randomly divided into six groups and treated with a commercial diet containing Mo, Cd or Mo combined with Cd. Kidneys were collected on days 30, 60, 90 and 120 for determining the expression of heat shock proteins (HSPs), including HSP60, HSP70 and HSP90 in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…2 Effects of Mo or/and Cd on the mRNA expression levels of NF-κB, COX-2, and TNF-α in duck spleens. a-c The effects of Mo-or/and Cdinduced changes in the mRNA levels of NF-κB, COX-2, and TNF-α, respectively study has shown that the mRNA expression levels of HSPs in combination groups of Mo and Cd were upregulated; pathological changes in kidney tissue were obvious and the Mo + Cd groups were much more toxic than a single poisoning group [12]. In the present work, mRNA expression of HSPs was upregulated in the experimental groups while the HSP expression was decreased in the HMo + Cd group at 120 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Effects of Mo or/and Cd on the mRNA expression levels of NF-κB, COX-2, and TNF-α in duck spleens. a-c The effects of Mo-or/and Cdinduced changes in the mRNA levels of NF-κB, COX-2, and TNF-α, respectively study has shown that the mRNA expression levels of HSPs in combination groups of Mo and Cd were upregulated; pathological changes in kidney tissue were obvious and the Mo + Cd groups were much more toxic than a single poisoning group [12]. In the present work, mRNA expression of HSPs was upregulated in the experimental groups while the HSP expression was decreased in the HMo + Cd group at 120 days.…”
Section: Discussionmentioning
confidence: 99%
“…Two hundred forty healthy 11-day-old ducks were randomly divided into six groups (n = 40 per group). A duck model of excessive exposure to Mo or/and Cd was developed as described in our previous publication [12]. Briefly, ducks in each group were fed with basal diet with different concentrations of Mo or/and Cd: control group (0 mg/kg Mo, 0 mg/kg Cd), low dietary intake of Mo group (LMo group, 15 mg/kg Mo), high dietary intake of Mo group (HMo group, 100 mg/kg Mo), Cd group (4 mg/kg Cd), LMo + Cd group (15 mg/kg Mo, 4 mg/kg Cd), and HMo + Cd group (100 mg/kg Mo, 4 mg/kg Cd).…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…Zhu et al found that Mn had a dose-dependent effect on Hsp27, Hsp40, Hsp60, Hsp70, and Hsp90 mRNA expression in chicken spleen lymphocytes in vitro [20]. The study of Xia et al showed that the high expression of Hsps played a role in the resistance of duck kidney toxicity induced by Mo and Cd [21]. Although our previous studies indicated that the higher Hsp levels were involved in the injury process of the liver, thymus, spleen, and bursa of Fabricius in chickens with Se deficiency [22][23][24], the effect of Se deficiency on Hsp levels was unknown in chicken erythrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Duck model of excessive exposure of Mo and Cd was developed as described in our previous publication [28]. Briefly, ducks in each group were fed with basal diet with different concentrations of Mo O) were added into the basal diet as the sources of Mo and Cd, respectively.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…Our previous study showed that the damage on kidneys co-induced by Mo and Cd were more serious than separate Mo or Cd when investigating the effects and mechanism of Mo combined with Cd on duck kidneys [28]. Furthermore, there is a bare study about the prolonged toxicity of Mo combined with Cd on the testicle, especially on waterfowl.…”
Section: Introductionmentioning
confidence: 99%